BMS-754807 is cytotoxic to non-small cell lung cancer cells and enhances the effects of platinum chemotherapeutics in the human lung cancer cell line A549. (December 2016) - Franks, S.; Jones, Robert; Briah, Ritesh; Murray, Payton; Moorehead, Roger
Abstract Background Despite advances in targeted therapy for lung cancer, survival for patients remains poor and lung cancer remains the leading cause of cancer-related deaths worldwide. The type I insulin-like growth factor receptor (IGF-IR) has emerged as a potential target for lung cancer treatment, however, clinical trials to date have provided disappointing results. Further research is needed to identify if certain patients would benefit from IGF-IR targeted therapies and the ideal approach to incorporate IGF-IR targeted agents with current therapies. Methods The dual IGF-IR/insulin receptor inhibitor, BMS-754807, was evaluated alone and in combination with platinum-based chemotherapeutics in two human non-small cell lung cancer (NSCLC) cell lines. Cell survival was determined using WST-1 assays and drug interaction was evaluated using Calcusyn software. Proliferation and apoptosis were determined using immunofluorescence for phospho-histone H3 and cleaved caspase 3, respectively. Results Treatment with BMS-754807 alone reduced cell survival and wound closure while enhancing apoptosis in both human lung cancer cell lines. These effects appear to be mediated through IGF-IR/IR signaling and, at least in part, through the PI3K/AKT pathway as administration of BMS-754807 to A549 or NCI-H358 cells significantly suppressed IGF-IR/IR and AKT phosphorylation. In addition of BMS-754807 enhanced the cytotoxic effects of carboplatin or cisplatin in a synergistic manner when given simultaneously to A549 cells. Conclusions BMS-754807 may be an effective therapeutic agent for the treatment of NSCLC, particularly in lung cancer cells expressing high levels of IGF-IR.